Differential Response to Low-Dose Dopamine or Low-Dose Nesiritide in Acute Heart Failure With Reduced or Preserved Ejection Fraction: Results From the ROSE AHF Trial (Renal Optimization Strategies Evaluation in Acute Heart Failure). (August 2016) - Wan, Siu-Hin; Stevens, Susanna R.; Borlaug, Barry A.; Anstrom, Kevin J.; Deswal, Anita; Felker, G. Michael; Givertz, Michael M.; Bart, Bradley A.; Tang, W.H. Wilson; Redfield, Margaret M.; Chen, Horng H.
Abstract : Background—: The ROSE AHF trial (Renal Optimization Strategies Evaluation in Acute Heart Failure) found that when compared with placebo, neither low-dose dopamine (2 µg/kg per minute) nor low-dose nesiritide (0.005 μg/kg per minute without bolus) enhanced decongestion or preserved renal function in AHF patients with renal dysfunction. However, there may be differential responses to vasoactive agents in AHF patients with reduced versus preserved ejection fraction (EF). This post hoc analysis examined potential interaction between treatment effect and EF (EF ⩽40% versus >40%) on the ROSE AHF end points. Methods and Results—: ROSE AHF enrolled AHF patients (n=360; any EF) with renal dysfunction. The coprimary end points were cumulative urine volume and the change in serum cystatin-C in 72 hours. The effect of dopamine (interaction P =0.001) and nesiritide (interaction P =0.039) on urine volume varied by EF group. In heart failure with reduced EF, urine volume was higher with active treatment versus placebo, whereas in heart failure with preserved EF, urine volume was lower with active treatment. The effect of dopamine and nesiritide on weight change, sodium excretion, and incidence of AHF treatment failure also varied by EF group (interaction P <0.05 for all). There was no interaction between vasoactive treatment's effect and EF on change in cystatin-C. Compared with placebo, dopamine was associated with improved clinical outcomes in heart failure with reduced EF and worse clinical outcomes in heart failure with preserved EF. With nesiritide, there were no differences in clinical outcomes when compared with placebo in both heart failure with reduced EF and heart failure with preserved EF. Conclusions—: In this post hoc analysis of ROSE AHF, the response to vasoactive therapies differed in patients with heart failure with reduced EF and heart failure with preserved EF. Investigations of AHF therapies should assess the potential for differential responses in AHF with preserved versus reduced EF. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01132846. Abstract : Supplemental Digital Content is available in the text.